Pelatihan Desain Konten Media Sosial Kreatif Untuk Promosi Kegiatan Gereja Bagi Muda-Mudi Gereja - Sihite, A M Hatuaon; Rajagukguk, Denni M; Sihombing, Monang Juanda Tua; Limbong, Riswan; Nadeak, Berto; Sembiring, Abdul Sani (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2025)
Active involvement of church youth in ministry is essential for fostering spiritual growth and creativity among Christian youth. In today's digital era, social media serves as a powerful platform to promote church activities in an engaging and modern way. However, many youths lack the skills to design content that is visually appealing and aligned with digital trends. This community service activity aimed to enhance the ability of the youth at GPP Church, Jl. Pelajar, Medan, in creating creative social media content using design applications such as Canva and CapCut. The implementation method included initial observation, hands-on training, mentoring, and evaluation of the participants' work. The results showed high enthusiasm from the participants and their ability to produce creative content in the form of posters, reels, and promotional church event designs. This training successfully improved their understanding and skills in designing and using social media positively to support church events and outreach. Furthermore, it empowered the youth to become creative digital ambassadors for the church, staying relevant to current technological developments.